Prevalence and Load of Cervical Ureaplasma Species With Respect to Intra-amniotic Complications in Women With Preterm Prelabor Rupture of Membranes Before 34 weeks - Kacerovsky, Marian; Kukla, Rudolf; Bolehovska, Radka; Bostik, Pavel; Matulova, Jana; Mls, Jan; Stranik, Jaroslav; Jacobsson, Bo; Musilova, Ivana (Frontiers in Pharmacology, 2022)
Objectives: To determine the prevalence and load of Ureaplasma spp. DNA in the cervical fluid of women with singleton pregnancies complicated by preterm prelabor rupture of membranes (PPROM) with respect to intra-amniotic infection, sterile intra-amniotic inflammation, and colonization of the amniotic fluid. Methods: A total of 217 women with PPROM between gestational ages 24 + 0 and 33 + 6 weeks were included in this study. Paired amniotic and cervical fluid samples were collected at the time of admission via transabdominal amniocentesis and using a Dacron polyester swab, respectively. Microbial invasion of the amniotic cavity was diagnosed using a combination of culture and molecular biology methods. Intra-amniotic inflammation was determined based on the concentration of interleukin-6 in the amniotic fluid. Based on the presence or absence of these conditions, the women were stratified into the following subgroups: intra-amniotic infection (with both), sterile intra-amniotic inflammation (with inflammation only), colonization (with microorganisms only), and negative amniotic fluid (without either). The Ureaplasma spp. DNA load in the cervical fluid was assessed using PCR. Results:Ureaplasma spp. DNA in the cervical fluid was found in 61% (133/217) of the women. Women with negative amniotic had similar prevalence of Ureaplasma spp. DNA in cervical fluid (55%) to those with sterile intra-amniotic inflammation (54%) but lower than those with intra-amniotic infection (73%) and colonization (86%; p < 0.0001). Women with negative amniotic fluid had a lower load of Ureaplasma spp. DNA in their cervical fluid (median: 4.7 × 103 copies of DNA/ml) than those with intra-amniotic infection (median: 2.8 × 105 copies DNA/ml), sterile intra-amniotic inflammation (median: 5.3 × 104 copies DNA/ml), and colonization (median: 1.2 × 105 copies DNA/mL; p < 0.0001). Conclusion: In conclusion, in PPROM at <34 weeks, the presence of intra-amniotic infection, sterile intra-amniotic inflammation, or colonization of the amniotic fluid was associated with a higher prevalence and/or load of Ureaplasma spp. DNA in the cervical fluid than the absence of intra-amniotic complications.